Hägnutnyttjande och beteende hos röd panda (Ailurus fulgens) på Nordens Ark - Ohlsson, Elin (2020)
The red panda is a carnivore who is specialized at feeding of bamboo. Bamboo is very low in nutrient and the red panda therefor need to forage through large parts of the day. They live in subtropical and temperate forests from Nepal in the west to China in the east. The red panda is considered endangered by the IUCN because it has decreased by 50 % the last 18 years. The biggest threat to the red panda is deforestation of their living area because the humans in the area uses the land for their livestock, farming and to build houses on.